2020
DOI: 10.3393/ac.2019.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Cavity Metastasis From Colorectal Cancer Represents End-Stage Disease and Should Be Palliated

Abstract: Nasal metastases from colorectal cancer is rare. The presentation of nasal metastases is often very similar to primary nasal sinus adenocarcinoma. A high index of suspicion is required, especially in patients who have had a previous history of colorectal carcinoma. Histology is ultimately required for diagnosis. We describe 2 cases of nasal metastases from colorectal carcinoma, and discuss the presentation, diagnosis and management of the case. Such metastatic disease ultimately represents end-stage malignancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…On the contrary, nasal metastases from colorectal primary carry a very poor prognosis and are usually fit for palliative treatment only. [9] Hence, differentiating between the two becomes very important. Due to the rarity of such cases, this case may help throw light on the importance of clinical, radiological, histopathological, and immunohistochemical features in diagnosing a nasal cavity mass in a pre-existing rectal adenocarcinoma as primary or metastatic.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, nasal metastases from colorectal primary carry a very poor prognosis and are usually fit for palliative treatment only. [9] Hence, differentiating between the two becomes very important. Due to the rarity of such cases, this case may help throw light on the importance of clinical, radiological, histopathological, and immunohistochemical features in diagnosing a nasal cavity mass in a pre-existing rectal adenocarcinoma as primary or metastatic.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that increased numbers of metastatic lesions and peritoneal involvements are associated with a poor prognosis of survival. In addition, tumor subtypes based on microsatellite instability and genetic alterations in KRAS, NRAS, or BRAF are crucial in understanding the biologic features of primary cancer and metastatic lesions [9]. With the development of molecular targeted agents and surgical techniques, multimodal treatments of mCRC have been advanced to improve survival and increase the efficacy of treatment [10].…”
Section: Introductionmentioning
confidence: 99%